Survey of the Burn Wound Healing by Iranian Traditional Medicine from the Herbalists or Herbal Medicine Vendors in the Mazandaran Province - E Nasiri; SJ Hosseinimehr; M Azadbakht; SA Madani (Institue of Medicinal Plants, ACECR, 2013)
Background: A Burn injury is a major health problem in the developing countries. Various treatments were applied for treatment of burn wounds by Iranian traditional medicine for thousands of years ago. Objective: The purpose of this study was to evaluate the natural products based on treatment of burn wounds by herbalists or herbal medicine vendors in the Mazandaran province. Methods: This research was a cross-sectional study and all herbalists or herbal medicine vendors were enrolled in this study. Snow ball sampling method was used with a questionnaire. Demographic data, methods of treatment for wounds, itching and pain were collected. The results were analysised. Results: In this study, 29 herbal and 4 animal based products were recommended by herbal medicine vendors for treatment of burn wounds. The results showed that 77 percent of respondents to treatment of burn wounds by natural products were recommended. Aloe Vera gel was the first choice for treatment of burn that was recommended by the herbalists. Conclusion: These results are interesting to find new drugs for treatment of burn wound healing with regards to Iranian traditional medicine. Since there are limited animal and clinical studies for approval of these natural products, future studies are needed for assessment of these traditional medicines for treatment of burn injuries.